An Improved Tunnel-Track Model in Saturated Poroelastic Soils to a Moving Point Load - Zunan Fu; Yuanlei Xu; Zonghao Yuan; Li Shi; Guoshuai Wang; Wenbo Song; Yanming Yu (Advances in Civil Engineering)
To predict the mechanical response of a circular cavity/tunnel buried in saturated poroelastic soils to a moving point load, a semianalytical model is provided in this work. The soils are governed by Biot’s theory that describes the wave propagations for saturated poroelastic materials. The displacement and stress vectors for the solid skeleton and pore-water fluid are represented by scalar and vectorial potentials. The governing equations for the tunnel and surrounding soils are solved in the frequency domain with the aid of separation of variables and Fourier transformations. To check the feasibility of the present analytical model, the solution is compared with other available results calculated for the ring load case. The good agreement shows the correctness of the present model. Numerical results suggest that the mechanical response from a moving point load in a tunnel for two-phase poroelastic materials is quite different from that in single-phase elastic materials. The critical velocity of the tunnel-soil system is around the shear wave speed of soils while the second one introduced into the track-tunnel-soil system with very high value is around the critical velocity of the track structure itself.